AR-Supported Induction Cooker AR-SI: One Step before the Food Robot - Ergun, Salih; Karadeniz, Ahmet Mert; Tanriseven, Sercan; Simsek, Ibadullah Yasin (2020 IEEE International Conference on Human-Machine Systems (ICHMS), 2020)
In recent years we are facing with new arising concepts in the gastronomy sector as a consequence of the new advancements in industry 4.0. Preparing food, cooking, serving and other gastronomic processes have evolved with the new trends blending IoT (Internet of Things), AR (Augmented reality), VR (Virtual Reality) and even robotics. In this paper we present an innovative concept named AR-SI. It's an AR-supported induction cooker presented as a preliminary study of a step before the food robot. AR-SI cooker is a holistic solution implemented with IoT and smart weight control which makes it possible to establish connected and distributed food practicing and adaptive power control in addition to AR support. The induction-based cooking is provided as an electronic kitchen appliance which forms the basis of cooking layout. This innovative holistic approach qualifies the AR-SI cooker through a virtual assistant that can be used for a distinguished interactive food preparation and training experience. The meal recipe is uttered explaining how to prepare the ingredients and cook with prescribed weight control. The recipe is animated by 3D graphics in augmented form on the actual cooker for the preparation of delicious meals.